Brain health advice in the news: managing notions of individual responsibility in media discourse on cognitive decline and dementia. Issue 1 (2nd January 2017) - Lawless, Michael; Augoustinos, Martha
ABSTRACT: Advice relating to the prevention of cognitive decline and dementia has become commonplace in the media. This article explores how messages about brain health are constructed in a sample of Australian newspapers from 2009 to 2014. Drawing on insights from discursive psychology and conversation analysis, we identify some specific discursive practices used in the media to construct advice and manage issues of responsibility for brain health. Advice-giving formulations fitted recognisable, scripted patterns to suggest a causal relationship between engaging in dementia preventative behaviour and individuals' risk of cognitive decline and dementia. We argue that the advice positioned audiences as individually responsible for brain health in older age and displayed complex moral claims regarding audiences' obligation to commit to brain enhancement and dementia preventative activities. The identified practices were also used to handle stakeholders' accountability for the general implications and prescriptive nature of their claims. Conclusions offer reflections on how social norms and expectations about brain health in old age are constructed and treated as accountable.